1991
DOI: 10.1037/0278-7393.17.4.664
|View full text |Cite
|
Sign up to set email alerts
|

Perseverant responding in speeded naming of pictures: It's in the links.

Abstract: Data are reported on picture naming under speeded deadline conditions. In Experiment 1, more errors were made in response to pictures with low-relative to high-frequency names, indicating that the deadline constrained name selection. In addition, subjects often made prime-related perseverative errors, in which they misnamed target pictures by giving them the names of related pictures that had been named previously (primes). In Experiment 2, prime-related perseverative errors did not occur at a greater than cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
174
4
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(198 citation statements)
references
References 65 publications
(89 reference statements)
16
174
4
4
Order By: Relevance
“…In accordance with previous studies (e.g., Damian et al, 2001;Schnur et al, 2006;Vitkovitch and Humphreys, 1991), we showed that pictures were named slower and responses were more erroneous in the context of the same-category items than in the context of items from different semantic categories. This semantic interference can be accounted for by competition between coactivated lexical entries in the same semantic context.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies (e.g., Damian et al, 2001;Schnur et al, 2006;Vitkovitch and Humphreys, 1991), we showed that pictures were named slower and responses were more erroneous in the context of the same-category items than in the context of items from different semantic categories. This semantic interference can be accounted for by competition between coactivated lexical entries in the same semantic context.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the fact that participants were instructed to try to "beat" the deadline, all reaction times were included in the analyses, provided that the words were pronounced correctly. This is the procedure used in other experiments with speeded naming of either words (Strain et al, 1995) or pictures (Vitkovitch & Humphreys, 1991). In all other respects, the procedure was identical to that in Experiment 1.…”
Section: Methodsmentioning
confidence: 99%
“…This is a parallel effort in English, Italian, Spanish, and Chinese, part of the continuing project "Cross-Linguistic Studies of Aphasia." In this regard, we are particularly interested in studies showing that the kinds of naming errors produced by aphasic patients can also be elicited in normal adults forced to name pictures under perceptual degradation (Laws, Leeson, & Gale, 2002) or under increasing time pressure (Vitkovitch & Humphreys, 1991;Vitkovitch, Humphreys, & Lloyd-Jones, 1993). In the present study, the partici-pants were asked to name the stimuli as fast as possible without making mistakes, and parameters were set to avoid inducing a speed/accuracy trade-off.…”
Section: Summary and Future Directionsmentioning
confidence: 99%